Evaluasi Kinerja Struktur Bangunan Rumah Sakit Jiwa Menggunakan Pushover Analysis - Novalia Ramadhani; Sapta Sapta; Robi Sahbar (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Structural concepts in the planning and evaluation of building structures for earthquakes emphasize performance, resilience, and rapid recovery. One such approach is performance-based design, known as Performance-Based Earthquake Engineering (PBEE). This research aims to design the structural system of a mental hospital building against seismic loads according to SNI 1726:2019 and to analyze the performance level of the specialized Psychiatric hospital structure following a design-level earthquake. The analysis was conducted by evaluating gravity loads, applying the equivalent static force method, performing response spectrum analysis, modeling the structure using ETABS, and checking the structure for strength, stiffness, and stability. The structural performance was evaluated using a non-linear pushover analysis. The results of this study indicate that the performance level of the Psychiatric hospital building structure, when subjected to a displacement of 0.59 m, exceeds the Collapse Prevention (CP) level.